2006
DOI: 10.1063/1.2177430
|View full text |Cite
|
Sign up to set email alerts
|

Leakage current of multiferroic (Bi0.6Tb0.3La0.1)FeO3 thin films grown at various oxygen pressures by pulsed laser deposition and annealing effect

Abstract: Thin films of multiferroic (Bi0.6Tb0.3La0.1)FeO3 were grown on Pt∕Ti∕SiO2∕Si substrate under various oxygen pressures by pulsed laser deposition technique. X-ray diffraction patterns show that the crystallinity of the thin film is improved with decreasing depositing oxygen pressure and the thin film grown at a lower oxygen pressure of 0.01torr exhibits a single perovskite phase with preferred (001) orientation. Leakage current of the as-deposited thin films decreases with decreasing grown oxygen pressure. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(104 citation statements)
references
References 21 publications
3
101
0
Order By: Relevance
“…The NRBS results clearly show that there are V O s in BFO films: 11.2% deficient in the asdeposited film and 6.0% deficient in post-annealed film compared to the ideal case. At the same time, the V O s can be effectively reduced by the post-annealing which is consistent with reported results (Wang et al, 2006). Furthermore, the leakage current densities of asdeposited and annealed BFO and BFO:SmO films were measured and shown as Fig.…”
Section: Physical Propertiessupporting
confidence: 77%
See 2 more Smart Citations
“…The NRBS results clearly show that there are V O s in BFO films: 11.2% deficient in the asdeposited film and 6.0% deficient in post-annealed film compared to the ideal case. At the same time, the V O s can be effectively reduced by the post-annealing which is consistent with reported results (Wang et al, 2006). Furthermore, the leakage current densities of asdeposited and annealed BFO and BFO:SmO films were measured and shown as Fig.…”
Section: Physical Propertiessupporting
confidence: 77%
“…Ferroelectric materials with lower leakage current typically exhibited smaller dielectric loss (Joshi, et al, 2000). For example, Wang et al reported that reduction of oxygen vacancies in doped BFO films reduced the leakage current and then the dielectric loss (Wang et al, 2006). Figure 9 shows the leakage current density vs. electric field (J-E) characteristics of BFO:SmO, BFO, and SmO thin films.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, various approaches have been proposed, such as reduction in oxygen vacancies, domination of the ohmic conduction, and intergrain depletion in grain boundary limited conduction. The efforts have been made to reduce the leakage current density by either introducing dopants or using different fabrication methods [12][13][14][15][16]. At present, many researchers are engaged in the enrichment of multiferroic properties of BiFeO 3 -relevant materials, using different trivalent dopants such as La [17], Mn [18], Sm [19] and Ti [20].…”
Section: Introductionmentioning
confidence: 99%
“…The ferroelectric loop of NCMO thin film could not be measured due to leakage current characteristics and it could be due to the existence of Mn 2þ and oxygen vacancies. 13 The magnetodielectric constant is defined as de MD ½eðHÞ À eð0Þ =eð0Þ, where e(H) and e(0) are the dielectric constants (e) under applied field and zero applied magnetic fields. The temperature dependence of de MD for 0.1 kOe and 0.5 kOe magnetic fields is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%